2019
DOI: 10.1371/journal.pone.0218152
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal prehabilitation to reduce the incidence of delirium and other adverse events in elderly patients undergoing elective major abdominal surgery: An uncontrolled before-and-after study

Abstract: Background Delirium is a common and serious complication in elderly patients undergoing major abdominal surgery, with significant adverse outcomes. Successful strategies or therapies to reduce the incidence of delirium are scarce. The objective of this study was to assess the role of prehabilitation in reducing the incidence of delirium in elderly patients. Methods A single-center uncontrolled before-and-after study was conducted, including patients aged 70 years or old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 59 publications
0
79
1
2
Order By: Relevance
“…The hematinic component of the prehabilitation program may not have contributed to the decreased incidence of delirium 10 because results of the present study do not present a difference in this outcome between both groups. However, based on the previous literature, a higher incidence of delirium could be expected in anemic patients compared with nonanemic patients.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The hematinic component of the prehabilitation program may not have contributed to the decreased incidence of delirium 10 because results of the present study do not present a difference in this outcome between both groups. However, based on the previous literature, a higher incidence of delirium could be expected in anemic patients compared with nonanemic patients.…”
Section: Discussioncontrasting
confidence: 46%
“…[6][7][8] Both CRC and AAA require abdominal surgery as definitive treatment and have been used together in studies on delirium after major abdominal surgery. [10][11][12] Delirium is the most frequent surgical complication and a common outcome after surgery for both CRC and AAA in older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usual prehabilitation programs that include physical and nutritional interventions have demonstrated to reduce the incidence of post-operative complications, shorten hospital stay and improve healthrelated quality of life [118,119], also in frail patients [120]. Regarding delirium, we are beginning to observe positive effects of prehabilitation programs with a reduction in delirium incidence [121], although more studies are needed.…”
Section: Delirium Prevention By Targeting Frailty With Physical Exercisementioning
confidence: 99%
“…Most trials report clinical outcomes through careful patient selection and elimination of emergent cases and those in need of urgent intervention. Janssen et al [23] has reported single centre uncontrolled before and after study including 627 patients aged 70 years and older and undergoing elective abdominal surgery for colorectal carcinoma or aortic aneurysm. The prehabilitation group received interventions to improve patients' physical health, nutritional status, frailty and anaemia prior to surgery.…”
Section: Prehabilitation In Hepato-pancreatico-biliary Surgerymentioning
confidence: 99%